Clowns acting in hospital stages (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This work consists of a presentation by the scenic artist Wellington Nogueira, founder of the Associação Doutores da Alegria, and an interview given by him transcribed in full. The interviewee narrates the development and insertion of professional clown in a hospital environment, since 1991. Promoting the investigation of new spatial configurations within hospitals, and in the field of clowning, as well as the establishment of artistic, human, political and social relations among artists and people in hospital situations, this phenomenon, based on the project brought to Brazil by Wellington Nogueira, was widely disseminated in the country, where hundreds of groups.
Keywords: Wellington Nogueira; Doctors of Joy; Interview